An on-line velocity flow profiling system using electrical resistance tomography - Long, Timothy Matthew (Department of Electrical Engineering, 2023)
A system to display velocity profiles of flows through the CPUT FPRC pipe test loop on-line has been developed. An electrical resistance tomography instrument developed at the University of Cape Town is used to generate conductivity profiles through cross sections of the flow in a 057mm pipe at two points, separated by either 50 or 100mm. The two concentration profiles are cross correlated on a pixel-wise basis to produce a velocity profile. The software was developed using C++ and employs a highly modular structure that allows different image reconstruction and cross correlation algorithms to be implemented without substantial changes to the rest of the application. Results showing the speed performance of the system are presented as well as typical velocity profiles from a sliding bed flow regime.